Pollen derived low molecular compounds enhance the human allergen specific immune response in vivo. Issue 10 (18th May 2016) - Gilles‐Stein, S.; Beck, I.; Chaker, A.; Bas, M.; McIntyre, M.; Cifuentes, L.; Petersen, A.; Gutermuth, J.; Schmidt‐Weber, C.; Behrendt, H.; Traidl‐Hoffmann, C.
Summary: Background: Besides allergens, pollen release bioactive, low molecular weight compounds that modulate and stimulate allergic reactions. Clinical relevance of these substances has not been investigated to date. Objective: To elucidate the effect of a non‐allergenic, low molecular weight factors from aqueous birch pollen extracts (Bet‐APE < 3 kDa) on the human allergic immune response in vivo . Methods: Birch and grass pollen allergic individuals underwent skin prick testing with allergen alone, allergen plus Bet‐APE < 3 kDa, or allergen plus pre‐identified candidate substances from low molecular pollen fraction. Nasal allergen challenges were performed in non‐atopic and pollen allergic individuals using a 3 day repeated threshold challenge battery. Subjects were either exposed to allergen alone or to allergen plus Bet‐APE< 3 kDa. Local cytokine levels, nasal secretion weights, nasal congestion and symptom scores were determined. Results: Skin prick test reactions to pollen elicited larger weals when allergens were tested together with the low molecular weight compounds from pollen. Similar results were obtained with candidate pollen‐associated lipid mediators. In nasal lining fluids of allergic patients challenged with allergen plus Bet‐APE < 3 kDa, IL‐8 and IgE was significantly increased as compared to allergen‐only challenged patients. These patients also produced increased amounts of total nasal secretion and reported more severe rhinorrhea than the allergen‐only challenged group. Conclusions: Low molecular compounds from pollen enhance the allergen specific immune response in the skin and nose. They are therefore of potential clinical relevance in allergic patients.